Web service proxy for web3D-based large-scale collaborative virtual environment - Li, ZhiYuan. (2009)
Large-scale Collaborative Virtual Environment (LCVE) provides a spatially large, content-rich, and evolving-enable virtual environment that can support a large number of simultaneous participants geographically dispersed over a wide area network, such as Internet. In a LCVE, a large number of simultaneous participants make CVE more popular and anyone, at the edge of network, can communicate and interact with each other freely and easily without any technical restriction. LCVE typically employs client-server based network architecture. The server is responsible for authenticating users, storing the stats of avatars and entities, performing scene synchronization, and carrying out multiple additional tasks. The client is responsible for providing rich 3D graphic interface and ease of user manipulation, reflecting users’ interaction and collaboration, and performing efficient communication with the server.